Association between time of delivery and composite adverse outcomes in pregnancies complicated by hypertensive disorders - Stephen M. Wagner; Han-Yang Chen; Megha Gupta; Matthew J. Bicocca; Hector Mendez-Figueroa; Suneet P. Chauhan (Taylor & Francis Group, 2021)
Introduction: A potential manner to lower the morbidity with the hypertensive disoreders of pregancy is to explore the time of day of delivery. Objective: To compare composite neonatal adverse outcomes among term women with hypertensive disorders. Methods: This population-based cohort study used the U.S. vital statistics dataset from 2013 to 2017. Time of delivery was categorized into three shifts. The primary outcome was composite neonatal adverse outcome.. Results: Compared to neonates delivered at the first shift, the risk of composite neonatal adverse outcome was higher at the third shift (aRR = 1.19, 95% CI = 1.13-1.25). Conclusion: the risk of composite neonatal adverse outcome is higher if the delivery occurs at the third (23:00-7:00) shift.